PERAN KEPERCAYAAN DIRI UNTUK MENGATASI KECEMASAN PARA FRESH GRADUATE DI BANTEN DALAM MENGHADAPI PERSAINGAN KERJA - Zahro, Siti Sulhah Husniyatul; Ratnaningtyas, Aisyah; Prastyani, Desy (Esa Unggul University, 2023)
High unemployment rates cause increased competition among job seekers. Job competition and uncertainty about getting a job after graduating from college can cause anxiety for new graduates. The anxiety that arises can be influenced by their self-confidence. This research aims to determine the effect of self-confidence on anxiety in facing job competition among fresh graduates in Banten. This research design is quantitative with a causal type and uses a purposive sampling technique with a sample size of 270 university and college graduates in Banten. The self-confidence measuring tool has a value of (α)=0.890 with 22 valid items, and the anxiety measuring tool has a value of (α)=0.865 with 23 valid items. This research used a simple linear regression analysis technique, and obtained results of sig. 0.000 and Y=87.205-0.397. This means that the hypothesis in this research is accepted. Self-confidence contributes 19.2% to anxiety when facing career competition, and the rest is influenced by other factors not examined in this research. New graduates with high anxiety were found in respondents who had applied for work more than 6 times (65%), had never attended training (76.6%), and had never had an internship (78.4%).